Mo Yan in Context : Nobel Laureate and Global Storyteller - Duran, Angelica; Huang, Yuhan (USA Purdue University Press)
This is the first English-language study of the Chinese writer$1 (Bs work and influence, featuring essays from scholars in a range of disciplines, from both China and the United States. Its introduction, twelve articles, and epilogue aim to deepen and widen critical discussions of both a specific literary author and the globalization of Chinese literature more generally. The book takes the (3z(Broot-seeking(3y (Bmovement with which Mo Yan$1 (Bs works are associated as a metaphor for its organizational structure. The four articles of (3z(BPart I: Leaves(3y (Bfocus on Mo Yan$1 (Bs works as world literature, exploring the long shadow his works have cast globally.s
English
Keywords: Literature; Buddhism; China; Mo Yan